The METODE LFC (LOST FOAM CASTING) PADA PROSES PEMBUATAN DIES ROLL PIPA 12 IN - Permata Ayu, Anisa; Jannati, Eidelweis Dewi (Universitas Majalengka, 2021)
Pipe dies roll is one of the important parts of a pipe roll bending machine that works as a bender or produces a radius of a metal pipe. The lost foam casting method or also called the Evaporative method is a casting method that uses Styrofoam as a more profitable pattern in small and medium industries because of the low initial capital costs with the same production capacity in other casting methods. so that this method is suitable to be implemented in the manufacture of small quantities of products and is able to form flexible and complex cast objects, one of which is in the manufacture of pipe roll dies. Keywords: Pipe dies roll, evaporative, casting